BIOACCUMULATION OF HEAVY METALS Cr AND Zn IN TILAPIA AND WATER LETTUCE FROM TREATED WATER BY AERATION METHOD (CASE STUDY : CIKAKEMBANG RIVER) - RACHMAWATI NIM: 25316002, MULKI
Cikakembang River is a tributary of Citarum River which is located in Majalaya District. The river receives waste effluents from the textile industry which contain heavy metals such as chromium and zinc. There was some treatment to improve water quality,, but it was still not effective in reducing heavy metal in river. Aeration method can be an alternative for water treatment which can reduce heavy metal. The purpose of this research was to determine the effect of aeration on heavy metal bioaccumulation on tilapia (Oreochromis niloticus) and water lettuce (Pistia stratiotes). Bioaccumulation experiment applied in a laboratory scale for 8 days. Measurement of concentration of heavy metals in fish and plants was done by extracting heavy metals in fish and plants on day 0, 1,4 and 8. From the results of the study, it was found that aeration was able to improve river water quality by increasing DO values until 3 times more, decreasing COD (93% removal), TSS (42% removal), TDS (52% removal), nitrate (19.1% removal), nitrite (3.5% removal), ammonium (75% removal), total phosphate (10% removal), phenol (23% removal) and Cr (94% removal) and Zn (50% removal). Initial aeration increased Cr accumulation in fish (BCF = 66.7) and Zn in fish (BCF = 1.3. In the plant aquarium system, initial aeration increased Cr accumulation (BCF = 3.39) and Zn (BCF = 4.9). In a combination of fish and plant aquarium systems, more plants accumulated Cr and Zn. Zn was more accumulated in plants (BCF = 4.9. Meanwhile, concentration of Cr and Zn in water decreased. Based on data, aeration process increases the bioavailability of Cr and Zn in fish and plants, so that to maximize the treatment of Cikakembang river water by aeration method, it is necessary to add waterplants that accumulate metal Cr and Zn.